Threat and Security Production at Václav Havel Airport Prague - Komasová, Sarah (Czech Journal of International Relations, 2019)
Building on empirical qualitative research, this article explores the nature of security and threat resulting from the contemporary security practice at Václav Havel Airport Prague. The article, building on Actor-Network Theory, interprets a security check as a chain of translation, the possibility of threat deployment as a program of action, and activities aiming to disable threats as a security antiprogram. Deployment of threats is further conceptualised as a failure of a security chain implementation, its design, threat program expectation, and the sole existence of a particular program. Considering inflight explosions as the main threat to be identified, the article proceeds by finding divergences between travellers and employees regarding the subject of protection, and analyses the notion of terrorism present in practice as well as its consequences. Security is then identified as a service of agency take-over. The article indicates the importance of security agency and the ANT-based inquiry enabling its exploration.